KAJIAN PUSTAKA : KESULITAN GURU TAMAN KANAK-KANAK DALAM MENGIMPLEMENTASIKAN PEMBELAJARAN MUSIK ANAK USIA DINI - Trifena Ruth Clara (Pusat Penelitian dan Pengabdian kepada Masyarakat STKIP Citra Bakti, 2026)
Music learning is a fundamental component of early childhood education as it contributes to children’s cognitive, linguistic, motor, and socio-emotional development. However, in practice, the implementation of music learning in kindergarten settings still encounters various challenges. This study aims to comprehensively examine the difficulties faced by teachers in implementing music learning in early childhood education based on research findings from the last ten years. The study employed a narrative literature review approach by analyzing national and international journal articles retrieved from Google Scholar, DOAJ, and Crossref databases. The results indicate that teachers’ difficulties are mainly related to limited musical competence, low confidence in teaching music, inadequate learning facilities, insufficient operational guidance in the curriculum, and limited access to professional training in music education. These findings suggest that the barriers to music learning implementation are not only technical but also structural and psychological. Therefore, policies supporting teacher competency development, facility provision, and continuous professional training are necessary to improve the quality of music education in early childhood settings. Keywords: music learning, kindergarten teachers, early childhood education, teacher competence, literature review.